(untitled) (Revista de Ciências Agroveterinárias, 2018)
The objective of this work was to evaluate the selectivity of fomesafen, in single application or in association with other herbicides, in pre-emergence of six cotton cultivars. Six experiments were conducted simultaneously in greenhouse conditions, in Red Oxisoil in water with pH of 5,9; 2,94% of OM and 320g kg-1 of clay. The experimental design was completely randomized with five replicates. Treatments were arranged in a factorial scheme (2 x 4) + 1, represented by two doses of fomesafen (375 and 500 g ha-1 - active ingredient) and association with diuron (1,25 kg ha-1 a.i.), trifluralin (1,80 kg ha-1 a.i.) and prometryn (1,25 kg ha-1 a.i.). A herbicide-free treatment was also added. At 30 days after the application of treatments, the cotton shoot was collected to quantify the dry mass accumulation. It was observed that the single fomesafen application or its association with diuron, trifluralin and prometryn affected the dry mass accumulation of the six cultivars. In general, the association of fomesafen with trifluralin was the most selective treatment. There is a differential response of cotton cultivars to fomesafen. The cultivar IMA CD 6001 LL was the most tolerant and IMA 8221 was the most sensible to fomesafen and its associations.